The Influence of the Pedagogical Factors on the Spiritual Becoming of Elder Teenagers - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2004)
The internalisation of spiritual values (truth, goodness, and beauty) shows the spiritual becoming of elder teenagers. The links between these values and pedagogical factors are established: between teachers’ humanistic competence and teenagers’ self-feeling at school. The teacher’s personality has the greatest influence on the cognitive level of internalisation of spiritual values. The deepest contact on all the levels of internalisation is with love of beauty, dignity, sensitiveness, honesty, and faith. The dominating (61.6 percent) subject relation with teachers insufficiently evokes the dispersion of the cognitive values (the dimension of truth), and has a slight influence on the internalisation of creativity and solidarity. However, the teenagers’ self-feeling at school most of all conditions the embodiment of these values (creativity, wisdom, and solidarity) on the behaviour level. Since the links of the values mentioned above with the other levels of internalisation are not stable, these values function mostly on the level of unrealized rules. The self-feeling at school has the closest links with the self-feeling in the family (x2 = 255,833, p < 0,000), with direct (x2 = 49,157, p < 0,000) and indirect contact with teachers: through the attitude towards studies (x2 = 53,361, p < 0,000), towards learning as the source of happiness (x2 = 63,649, p < 0,000), and towards making a progress (x2 = 86,943, p < 0,000). Besides, teachers rouse the least pupils’ anxiety. The contact with the contemporaries has influence on self-feeling at home, too (x2 = 30,676, p < 0,000). The pedagogical factors have a considerable influence on the spiritual becoming of elder teenagers.